Determination of heavy metals content in planted pucuk paku and pucuk ubi collected at various distances from pollution source / Erma Hafiza Ibrahim @ Abd Aziz - Ibrahim @ Abd Aziz, Erma Hafiza (2017)
The concentrations of heavy metals such as Zn, Fe, Cd and Cu were studied using atomic absorption spectrometer (AAS) on planted vegetable samples which were pucuk paku and pucuk ubi. Wet digestion method was used to extract the heavy metals in vegetables. Twelve samples were obtained at various distances which were 1 km, 2 km and 3 km from pollution source. At each distance, two samples of pucuk paku (pucuk paku at point 1 and pucuk paku at point 2) and two samples of pucuk ubi (pucuk ubi at point 1 and pucuk ubi at point 2) were collected. These points 1 and 2 refer to the different directions within the same distance. Samples were then analysed and compared with permissible limit from WHO. It was found that, only two samples were below the permissible limit which were pucuk paku point 1 at 3 km distance (for Zn which was 11.75 mg/kg and for Fe which was 3.250 mg/kg). The rest of the samples for all elements exceeded the safe limit provided by World Health Organization (WHO). In this study, the concentrations of Zn, Fe and Cd were shown to decrease with increase in distance. But, Cu was vice versa whereby increase in distance causes the concentration of Cu in vegetables to increase.